International accessibility and rental levels: a case study for the office-market in the Netherlands - Hugo Gordijn; Michiel Adriaan de Bok (European Regional Science Association (ERSA), 2002)
Rental levels of office floor space are determined by aspects of the buildings and aspects of the location. In this contribution we focus on the characteristics of locations using a large database of market-transactions. Accessibility proves to have an important impact on price levels. In particular the most expensive locations must have an excellent international accessibility by Air. Empirical results are presented.
Keywords: 330